Teachers' Perception for Integrating Educational Robots and Use as Teaching Assistants in Thai Primary Schools - Kajornpong Poolsawad; Noawanit Songkram; Krerk Piromsopa; Nutthakorn Songkram (Emerging Science Journal, 2020)
This study focused on teachers' perception for integrating educational robots into learning and the feedback of teachers and students who used an education robot prototype as a part of learning. Data were collected from 510 primary school teachers who were used in a confirmatory analysis of factor model. Confirmatory Factor Analysis (CFA) indicated a good fit with a six-factor model in the observed data, which could be presented through six dimensions of robotic education quality, including social interaction, cognitive function, teaching method, learner characteristics, main features, and content. The prototype-testing phase was carried out using 5th grade students at a primary school in Thailand. The robot was tested for 10 hours, which included 20 students participating in the focus group. The research results showed that integrating the six dimensions of robotic education into the educational robot prototype resulted in a strong positive improvement in the focus groups learners' behavior and supported the instructors during the learning process. In contrast, some teachers lacked experience and confidence with robots integrated with LMS, which caused challenging obstacles in teaching. The results were achieved when integrating the six-factor model into education robots to improve student learning. Future researchers should expand their studies to look into the opportunities and challenges that teachers and school administrators face in the classroom. Doi: 10.28991/esj-2021-SP1-09 Full Text: PDF